The Relationship between Application of GERMAS (Community Movement) Hand Washing with Water and Soap Simultaneously with Diarrhea in Primary School Students - Deno Harmanto; Nengke Puspita Sari (Jurnal Sains Kesehatan, 2019)
Diarrhea disease in Indonesia is still one of the endemic diseases and still often causes extraordinary events (outbreaks) in the community. This study aimed to study the relationship between the application of Germas (Community Movement) hands washing with running water and soap simultaneously with the occurrence of diarrhea in SDN 108 students in Seluma Regency. The type of research used was Analytical Survey using Cross Sectional design.. Samples  of  this study were 167 students in grades 4, 5, and 6 of  SDN 108 Seluma Regency. Sampling in this study used a Total Sampling technique. Data collection techniques in this study using primary data by interview using a questionnaire. The statistical test used is Chi-Square. The results showed that of 167 students, there were 113 students (67.7%) who did not experience diarrhea, 123 students (73.7%) had poor hands washing with and running water and soap, and there was a relationship between hands washing use soap and running water and soap with diarrhea. Keywords: diarrhea, germas,hands washing, soap